Motivating attendee's participation in distance learning via an automatic messaging plugin for the moodle platform - De Almeida, Luciano R.; Da Costa, João Paulo C.L.; De Sousa, Rafael T.; De Freitas, Edison P.; Canedo, Edna D.; Prettz, Juliano; Zacarias, Eliakim; Del Galdo, Giovanni (Proceedings - Frontiers in Education Conference, FIE, 2016)
Technological advances in information and communications systems are enabling access to education for millions of students, regardless of their geographical location. In this sense, distance learning schools take advantage of technological tools, such as course management systems (CMS) and their plugins. This work proposes a plugin for the e-learning platform Moodle that automatically sends e-mail messages to the students in order to motivate them to take part in the distance learning courses and, consequently, to reduce the dropout rates. This plugin has been tested in courses promoted by the General Coordination of Distance Education (CGEAD) of the Brazilian National School of Public Administration (ENAP). Based on data from its operation within the real ENAP distance learning environment, the proposed plugin is particularly successful to tackle the enrollment locking cases that compose the student dropout rate and also to motivate course enrolled students to access the virtual learning system more frequently.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Automatic messaging; Distance learning motivating tool; Moodle plugin